Menjadi Generasi Enterpreneur Muda: Kreatif, Mandiri, Inovatif - Afin Saputra; Ameliza Azzahra; Nurullijah .; Veta Lidya Delimah Pasaribu (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Human resources (HR) excellence is a top development priority in many countries around the world, including Indonesia, especially in facing various digital economic challenges that demand young generations to be creative, independent, and innovative. SMA Pelita Bangsa, as one of the schools in an urban area, plays a crucial role in the development of the young generation, who in the future will take on an important role in Indonesia's economy. However, in carrying out its role, SMA Pelita Bangsa faces various complex challenges, such as the low interest of students in entrepreneurship, the impact of a lack of understanding of the entrepreneurial world, limited access to training, and a school curriculum that does not adequately support access to the business world. Teachers and school administrators play a key role in shaping the entrepreneurial spirit within students. However, this is hindered by insufficient resources and a lack of well-integrated development programs.The Community Service Program (PKM) organized by students of Universitas Pamulang aims to analyze and strengthen the entrepreneurial spirit among SMA Pelita Bangsa students through the delivery of materials and a discussion themed “Becoming a Young Entrepreneurial Generation: Creative, Independent, Innovative.” With a participatory approach, this PKM activity will examine students’ knowledge and interest in the business world, as well as identify opportunities and challenges that influence their interest in entrepreneurship. This activity is expected to provide insights and sustainable positive impacts, not merely short-term solutions.The method used was a participatory approach through material delivery and interactive discussion for 2 class hours, running from 13:30 to 15:15 on Thursday, September 18, 2025, and involving 75 students divided into 3 classes. Observations showed high interest among several students, as evidenced by some students who already run small businesses. This enthusiasm became more apparent when they were able to present their small business experiences, such as fried chicken (ayam geprek) businesses or simple t-shirt screen-printing designs. This indicates a very large potential for the development of young entrepreneurs. However, the school still faces major challenges, as many students still have limited knowledge and lack interest in the business world. Another major issue is related to students’ independence and innovation, which are still very limited. It was observed that students who have businesses are still highly dependent on others as distributors and initiators of those businesses. The majority of students also feel more comfortable being consumers rather than producers, and only a few are able to express new business ideas and identify simple business opportunities around them. This PKM is expected to be an initial step in fostering students’ independence and innovation, as well as providing a practical learning model that can be applied to strengthen the entrepreneurial spirit among the young generation. Furthermore, this activity also has the potential to serve as a reference for other secondary schools in designing similar programs and make a tangible contribution to the efforts of developing creative and competitive human resources in Indonesia.